THE EFFECT OF PEDAL EXERCISE AND STRETCHING CALF MUSCLES MORE EFFECTIVE TO INCREASE THRESHOLD OF CALF MUSCLE PAIN ON THE FABRIC CUTTERS WORKER IN KEDIRI TABANAN - Sari, Ni Putu Ayu Sasmita; Winaya, I Made Niko; Griadhi, I Putu Adiartha; Adiatmika, I Putu Gede (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 1 (2018): Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Stands work attitude in a long time cause muscle complaints on fabric cutters worker. The purpose of this study is knowing whether effect of pedal exercise and stretching calf muscles more effective to increase threshold of calf muscle pain on the fabric cutters worker. Measurement of the value of pain was measured using a sphygmomanometer This study is experimental research using Pre Test and Post Test Control Group Design. These samples included 20 people who were divided into group treatment and group control. Group treatment was given pedal exercise and stretching calf muscles, while Group control without treatment. Hypothesis test by paired sample t-test in group treatment is p=0.000 with a mean difference 30.00±16.99, that mean is it can increase threshold of calf muscle pain, while in control group is p=0.758 with a mean difference 1.00±9.94, that mean is it can’t increase threshold of calf muscle pain. At different test between treatment group and control group using independent sample t-test was obtained p=0.000 (p<0.05). Based on these results, it can be concluded that pedal exercise and stretching calf muscles more effective to increase threshold of calf muscle pain. Keywords: pedal exercise, stretching, calf muscle pain, fabric cutter